АСПЕКТЫ БИОЛОГИИ РАЗМНОЖЕНИЯ SCAPHARCA INAEQUIVALVIS (BRUGUIÈRE) (BIVALVIA, ARCIDAE) В ЧЕРНОМ МОРЕ - (:unkn) unknown (Севастополь: ЭКОСИ-Гидрофизика, 2003)
Приведены результаты изучения репродуктивного цикла, темпов роста, возраста наступления половой зрелости и плодовитости вселившегося в Черное море моллюска Scapharca inaequivalvis (Bruguière, 1789).
Some features of reproduction biology of Scapharca inaequivalvis (Bruguière) (Bivalvia, Arcidae) in the Black Sea
The reproduction cycle, the growth rate and the sexual maturation age and also productivity of Scapharca inaequivalvis (Bruguière, 1789) from the Black Sea have been studied.